Determination of Suspects in Narcotics Crimes Through Supervised Submission (Controlled Delivery) - Tornado, Anang Shophan (Scholar Center, 2023)
Abstract Considering that the crime of illicit drug trafficking is already very horrific, both coming from abroad and those circulating within the country, a special method is needed to deal with it. Narcotics and psychotropics are substances or drugs that are very useful and necessary for certain diseases. However, if it is misused or used not in accordance with the standard of treatment, it can have very detrimental consequences for individuals or society, especially the younger generation. Seeing the difficulty of the investigative process for disclosing drug cases, there must be special rules governing the process or authority of investigators in handling drug cases. The authority of investigators in carrying out investigations, these techniques are undercover buys and controlled delivery. The norms governing controlled delivery, namely the Narcotics Law and the technical regulations under it, still cannot clearly describe the problems above, especially how the recipient, who incidentally is a person, is intentionally used or framed to become a recipient of narcotic packages .